Designing the Klotok Siring Application: Digitalizing Tourist Transportation in Banjarmasin City - latif, Abdul; Ratna Lindawati (INSTALL: Information System and Technology Journal, 2024)
Online klotok booking applications provide a more effective alternative. Through this system, tourists can view available klotoks, select schedules, make digital payments, and receive automatic booking notifications. Klotok owners can also manage reservations more easily and optimize their income. Siring Banjarmasin is one of the top tourist destinations in Banjarmasin City, offering a unique experience of exploring the river using a klotok a traditional boat from Kalimantan. Tourists can enjoy the scenic views of the Martapura River, visit floating markets, and experience the distinctive atmosphere of the city known as the "City of a Thousand Rivers."